Building Tourist Loyalty Through Brand Elements: The Mediating Role of Destination Image in Demak Islamic Heritage Tourism - Saifudin, Saifudin; Hartiningsih, Sepia; Rosalinda, Monika; Meisaroh, Putri (Institut Agama Islam Negeri Kendari, 2024)
This study investigates how destination brand elements influence tourist loyalty in Islamic heritage tourism, with a particular focus on the mediating role of destination image. Using Demak - a historically significant Islamic city in Indonesia - as a case study, the research examines the relationships between brand awareness, brand quality, destination image, and tourist loyalty. Data was collected through a quantitative survey of 112 tourists from seven Indonesian provinces representing diverse demographic backgrounds. The analysis employs structural equation modelling with Partial Least Square (SEM-PLS) to test the hypothesized relationships. The findings reveal that destination image and brand quality significantly influence tourist loyalty, while brand awareness shows an indirect effect through destination image mediation. Notably, the study demonstrates that destination image serves as a crucial mediating factor in translating both brand awareness and brand quality into tourist loyalty. These results contribute to our understanding of brand management in religious tourism contexts and provide practical implications for destination managers seeking to enhance tourist loyalty. The study suggests that building strong destination loyalty requires not only developing quality tourism products but also cultivating a positive destination image that resonates with religious and cultural values.